2009
DOI: 10.1016/j.cub.2009.06.055
|View full text |Cite
|
Sign up to set email alerts
|

Lack of DREAM Protein Enhances Learning and Memory and Slows Brain Aging

Abstract: In this paper, we reported evidence that a protein variously called DREAM/Calsenilin/KChip3 controls learning and memory in mice. It has been brought to our attention that the antibody against DREAM (FL-214, Santa Cruz sc-9142, lot #B230) that we used for expression analyses in genetically confirmed knockout mice (Figure 3B), as a specificity control in studies of DREAM-DNA binding (Figure 3A, lane 1), and for DREAM-CREB-CBP interactions (Figure 3C, lanes 4, 9, and 14) might on western blots also detect other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
4
1
Order By: Relevance
“…Notably, one study has suggested transcriptional repressor DREAM (Carrió n et al, 1999) to be involved in the regulation of CREB1-dependent mBDNF exon IV mRNA expression (Fontán-Lozano et al, 2009). However, we did not detect involvement of DREAM proteins in the regulation of hBDNF pIV in rat cultured cortical neurons with EMSA, using abs specific for the DREAM family members (supplemental Fig.…”
Section: Creb Arnt2-npas4 and Usfs Are The Key Factors Required For Activation Of Human Bdnf Promoter IV By Neuronal Activitycontrasting
confidence: 53%
See 1 more Smart Citation
“…Notably, one study has suggested transcriptional repressor DREAM (Carrió n et al, 1999) to be involved in the regulation of CREB1-dependent mBDNF exon IV mRNA expression (Fontán-Lozano et al, 2009). However, we did not detect involvement of DREAM proteins in the regulation of hBDNF pIV in rat cultured cortical neurons with EMSA, using abs specific for the DREAM family members (supplemental Fig.…”
Section: Creb Arnt2-npas4 and Usfs Are The Key Factors Required For Activation Of Human Bdnf Promoter IV By Neuronal Activitycontrasting
confidence: 53%
“…These results differed from the results described earlier (Jiang et al, 2008;Vashishta et al, 2009), but could be explained by use of glutamate receptor agonists instead of KCl-mediated depolarization for modeling neuronal activation in previous studies. In addition, we found that, at least in primary neurons, the DREAM family TFs do not contribute to activity-dependent regulation of hBDNF pIV as has been proposed for mBDNF pIV (Fontán-Lozano et al, 2009). Again, further experiments are needed to elucidate these issues.…”
Section: Discussionmentioning
confidence: 65%
“…Thus it has been suggested that DREAM gene knockout mice may not be suitable for the study of pain mechanisms as they are not reflective of the actual pain processing mechanisms that are being observed in this and other similar studies [18]. In addition, recent findings show that the DREAM gene knockout mice exhibit markedly enhanced learning and synaptic plasticity related to improved cognition capacities compared to the wild type mice [19]. This characteristic of DREAM gene knockout mice probably can also contribute to discrepancy to the finding in this study and other similar studies when compared to DREAM knockout mice.…”
Section: Discussionmentioning
confidence: 89%
“…Kv4 channel currents in cortical pyramidal neurons are modestly decreased in kchip3 À/À mice (Norris et al 2010). Dream À/À and kchip3 À/À mice exhibit enhanced hippocampal-dependent learning (Alexander et al 2009;Fontán-Lozano et al 2009), potentially through facilitation of CREB-dependent transcription (Fontán-Lozano et al 2009). Estradiolenhanced memory formation also appears to be modulated by DREAM (Tunur et al 2013).…”
Section: Physiological Functionsmentioning
confidence: 99%